Camping out - Amery, Heather; Cartwright, Stephen, 1947- (London : Usborne, 2004)
Poppy and Sam try their hand at camping when visitors come to their Apple Tree farm.
1.5
K-3
Keywords: Camping -- Juvenile fiction; Domestic animals -- Juvenile fiction; Families -- Juvenile fiction; Farm life -- Juvenile fiction; Camping -- Fiction; Domestic animals -- Fiction; Family life -- Fiction; Farm life -- Fiction; Camping -- Fiction; Domestic animals -- Fiction; Family life -- Fiction; Farm life -- Fiction